Relief design for laboratories and pilot plants. Issue 1 (5th October 2012) - Mize, Jennifer F.
<x xml:space="preserve">Abstract</x> Relief designs for laboratories and pilot plants present unique challenges to the relief designer. For example, the relief designer must consider the need for operational flexibility while designing a relief system that provides protection for current and future modes of operation. Therefore, small‐scale relief designs must address a wider range of potential overpressure scenarios due to the variations in chemistry that are routinely conducted within the laboratory or pilot unit. The small scale of laboratory and pilot plant operations present a significant challenge to the relief designer in selecting and designing effective relief systems. This article gives information for designing laboratory and pilot plant relief systems including: identification of relief scenarios, sizing calculation methods, relief devices, effluent discharge designs, and other protective system considerations. © 2012 American Institute of Chemical Engineers Process Saf Prog 32: 25–27, 2013.